1993
DOI: 10.1002/bies.950150405
|View full text |Cite
|
Sign up to set email alerts
|

Genes controlling nucleotide excision repair in eukaryotic cells

Abstract: The maintenance of genetic integrity is of vital importance to all living organisms. However, DNA--the carrier of genetic information--is continuously subject to damage induced by numerous agents from the environment and endogenous cellular metabolites. To prevent the deleterious consequences of DNA injury, an intricate network of repair systems has evolved. The biological impact of these repair mechanisms is illustrated by a number of genetic diseases that are characterized by a defect in one of the repair ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 53 publications
1
18
0
1
Order By: Relevance
“…One intriguing speculation is that RAD3 and its mammalian homolog XPD (60,67) are both involved in the maintenance of genome integrity. This would give further support to previous observations (56) that, like several other DNA repair pathways (12,68), recombination is conserved in S. cerevisiae and humans.…”
Section: Discussionsupporting
confidence: 90%
“…One intriguing speculation is that RAD3 and its mammalian homolog XPD (60,67) are both involved in the maintenance of genome integrity. This would give further support to previous observations (56) that, like several other DNA repair pathways (12,68), recombination is conserved in S. cerevisiae and humans.…”
Section: Discussionsupporting
confidence: 90%
“…However, our finding that mutations in p53 alter global but not transcription-coupled DNA repair suggests potential targets. For example, a number of genes have now been identified that encode different proteins involved in human NER, which when mutated are responsible for the different complementation groups of the human NERdeficiency syndromes xeroderma pigmentosum (XP) and Cockayne syndrome (CS) (22). The resultant repair deficiency in cells from each complementation group depends upon the function of the altered gene product, and certain groups exhibit selective deficiencies in either overall or transcriptioncoupled repair.…”
Section: Methodsmentioning
confidence: 99%
“…The XPD gene that encodes a helicase, a subunit of transcription factor IIH (TFIIH), is responsible for opening DNA around the damaged site, a crucial step in initiating the NER process (Egly 2001), which repairs bulky adducts and UV-induced DNA damage (Weeda and Hoeijmakers 1993). Several XPD polymorphisms in the coding regions have been identiWed (Shen et al 1998), including two single nucleotide polymorphisms, Asp312Asn in exon 10 and Lys751Gln in exon 23.…”
Section: Introductionmentioning
confidence: 99%